2004
DOI: 10.1002/eat.10263
|View full text |Cite
|
Sign up to set email alerts
|

Selective mood‐induced body image disparagement and enhancement effects: Are they due to cognitive priming or subjective mood?

Abstract: The findings yielded support for the cognitive priming hypothesis but not for the subjective mood hypothesis. Further means of examining the cognitive priming hypothesis were outlined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Other studies have shown that depression can lead to body image disturbance [ 12 , 13 , 15 ]. However, the temporal sequence is a potential major limitation of those studies as well, as they also used a cross sectional design.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have shown that depression can lead to body image disturbance [ 12 , 13 , 15 ]. However, the temporal sequence is a potential major limitation of those studies as well, as they also used a cross sectional design.…”
Section: Discussionmentioning
confidence: 99%
“…Results of some studies have shown that body image disturbance is associated with depression [ 8 , 10 , 16 , 17 ]. Other researchers suggest that depression predisposes to body image disturbance [ 12 , 13 , 15 ]. However, these previous studies had a cross sectional design, which does not assure the temporal sequence of the association investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These suggestions are in the line with those outlined by Stice et al (2003) with regards to weight control programs; they stressed the importance of increasing body satisfaction in young people. Likewise, Rotenberg et al (2004) demostrated the difficulty of modifying aspects related to the subjective state of mind by induction, despite achieving changes in the cognitive area with regards to body image.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to this connection, the literature shows that anxiety and depressive states influence body-image disturbances, usually increasing levels of body overestimation and especially body dissatisfaction. [58][59][60] What is more, mood changes during the day are closely associated with concurrent body-image disturbances. In this validation of the VR environments, ED patients displayed higher levels of anxiety and depressed mood after eating (in both the high-and low-calorie-food modes) and after visiting the swimming pool than in the neutral room.…”
mentioning
confidence: 99%